Performance in information processing speed is associated with parietal white matter tract integrity in multiple sclerosis - Grothe, Matthias; Jochem, Katharina; Strauss, Sebastian; Langner, Sönke; Kirsch, Michael; Hoffeld, Kai; Penner, Iris Katharina; Nagels, Guy; Klepzig, Kai; Domin, Martin; Lotze, Martin (Frontiers in Neurology, 2022)
Background: The Symbol Digit Modalities Test (SDMT) is most frequently used to test processing speed in patients with multiple sclerosis (MS). Functional imaging studies emphasize the importance of frontal and parietal areas for task performance, but the influence of frontoparietal tracts is not well characterized. We were interested in tract-specific characteristics and their association with processing speed in MS patients. Methods: Diffusion tensor imaging was obtained in 100 MS patients and 24 healthy matched controls to compare seed-based tract characteristics descending from the superior parietal lobule (Brodman area 7A [BA7A]), atlas-based tract characteristics from the superior longitudinal fasciculus (SLF), and control tract characteristics from the corticospinal tract (CST) and their respective association with ability on the SDMT. Results: Patients had decreased performance on the SDMT and decreased white matter volume (each p<0.05). The mean fractional anisotropy (FA) for the BA7A tract and CST (p<0.05), but not the SLF, differed between MS patients and controls. Furthermore, only the FA of the SLF was positively associated with SDMT performance even after exclusion of the lesions within the tract (r=0.25, p<0.05). However, only disease disability and total white matter volume were associated with information processing speed in a linear regression model. Conclusions: Processing speed in MS is associated with the structural integrity of frontoparietal white matter tracts.